Using Composite Resin Inclined Plane for the Repositioning of a Laterally Luxated Primary Incisor: A Case Report - Arikan, Volkan; Sari, Saziye (European Journal of Dentistry, 2011)
This case report describes the repositioning of a laterally luxated primary central incisor with occlusal interference, using a composite inclined plane. The patient was a 4-year-old girl who applied to our clinic three days after the injury. Because of the time delay between injury and presentation, it was not possible to reposition the tooth with pressure. Following a root-canal treatment, an inclined plane was prepared on the lower primary incisors, using composite resin. The tooth was repositioned in two weeks, and the inclined plane was then removed. After 1 year of follow-up, the treatment was found to be successful, both clinically and radiographically. The use of a composite inclined plane, accompanied by careful follow-up, is an effective alternative to extraction for laterally luxated primary incisors with occlusal interference. (Eur J Dent 2011;5:117-120)
Keywords: Inclined plane; Primary teeth; Dental trauma